Media Gamification and Learning Evaluation in Indonesian Language MPK Courses at Ganesha University of Education - Kadek Wirahyuni; Ida Bagus Putrayasa; I Wayan Rasna; I Nengah Suandi (ASIAN: Indonesian Journal of Learning Development and Innovation, 2024)
The purpose of this research is to (1) find out gamification as media and learning evaluation in Indonesian language MPK courses at Ganesha University of Education. The research method used in this research is descriptive analytical method with qualitative approach. The data collection techniques used are observation, interview, and documentation. The location of this research is at Ganesha University of Education. The research subjects were students who took MPK Indonesian Language courses at Ganesha University of Education. The results and discussion there are several applications to support learning in Indonesian language MPK courses, namely, Blooket, Gimkit, Kahoot, Quizwhizzer, Wordwall, and Oodlu. Student grades using gamification increased from an average of 7.5 to 8.5. Gamification with various applications is able to increase the positive attitude of students in learning Indonesian at Undiksha.